Finding the right franchise opportunity - a framework to increase the success rate of a franchise opportunity. - Chua, Ivor Tjun Tat. (2008)
Development of a framework through exploratory research and valuable insights from industry experts and academics, to find the right franchise opportunity for a potential franchisee by increasing the success rate.